Additive Manufacturing - Pou, Juan, editor 651720; Riveiro, Antonio, editor 651721; Davim, J. Paulo, editor 207699; ScienceDirect (Online service) 7722 ([Place of publication not identified] : Elsevier, 2021)
Additive Manufacturing explains the background theory, working principles, technical specifications, and latest developments in a wide range of additive manufacturing techniques. Topics addressed include treatments of manufactured parts, surface characterization, and the effects of surface treatments on mechanical behavior. Many different perspectives are covered, including design aspects, technologies, materials and sustainability. Experts in both academia and industry contribute to this comprehensive guide, combining theoretical developments with practical improvements from R&D. This unique guide allows readers to compare the characteristics of different processes, understand how they work, and provide parameters for their effective implementation. This book is part of a four-volume set entitled Handbooks in Advanced Manufacturing. Other titles in the set include Advanced Machining and Finishing, Advanced Welding and Deformation, and Sustainable Manufacturing Processes.